Differences in Perception of Economic, Social and Environmental Impacts for Tourism in Four Groups of Interests. Case Study Kosovo - DAUTI, Merita Begolli (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017, 2017)
Tourism is one of the complex activities of today’s modern society. In developed countries but also in some states as our country Kosova, country in process of transition in which export could be important product and employment generator. Even though Kosova is new state we still don’t have strategy for Tourism Development where achieving its goal will be sustainable use of natural and cultural resources, as crucial for tourism development and at the same time to prevent use of resources with negative irreversible consequences. This study aims to analyse if exists differences in perceptions of tourism impacts in Kosova between four groups of interests: economic operators of tourism, governmental and non-governmental agencies, local community and tourists. Data was collected from four groups of interests using questionnaires directed to 160 surveyed businesses, 35 surveyed governmental, non-governmental and local agencies, 382 surveyed residents and 378 surveyed tourists. Results of questionnaires were extracted using one-way ANOVA test and to see in specific manner differences between groups was used post-hoc test Scheffe method.